American Polisy Towards the Two-Year War in Lebanon (1975 -1976) - Khalil Ali Murad; Shahab Ahmad Rahman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The purpose of this research is to follow up and analyze U. S. A policy towards what was known as Two – Year War in Lebanon ( 1975 – 1976 ).Despite the decline of Lebanon position in American policy in the Middle East since the Arab – Israeli war in October 1973, but the possible repercussions of the war in Lebanon on Israel’s security on the hand, and on American efforts to find a peaceful settlement for Arab – Israeli conflict on the other hand , made Washington keen not to expand the war in Lebanon and try to find a political solution for it in any way. This explains Washington acceptance of the Syrian military intervention in Lebanon on April 5, 1976 and persuading her ally Israel not to oppose that intervention as long as it ensures that Syria does not exceed the red lines agreed upon by both sides, so that this intervention does not turn into a direct threat to Israel’s security. The Research sheds light on the outbreak of civil war in Lebanon in 1975, and the rapid developments in Lebanon in terms of political and security aspects with the expansion and intensification of the war, and U. S. A. policy toward those developments before and after the Syrian military intervention. The research was based on many sources in English and Arabic languages, among them the documents of U. S. department of state and the CIA, memoires of Lebanese and American politicians, academic studies and Lebanese newspapers.